2000
DOI: 10.1016/s0735-1097(00)00912-8
|View full text |Cite
|
Sign up to set email alerts
|

High levels of plasma brain natriuretic peptide and interleukin-6 after optimized treatment for heart failure are independent risk factors for morbidity and mortality in patients with congestive heart failure

Abstract: These findings indicate that high plasma BNP and IL-6 levels three months after optimized treatment are independent risk factors for mortality in patients with CHF, suggesting that sustained high plasma levels of BNP and IL-6 after additional standard treatment were independent risk factors for mortality in patients with CHF despite improvements in LVEF and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
249
5
15

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 375 publications
(284 citation statements)
references
References 33 publications
12
249
5
15
Order By: Relevance
“…This finding is in line with an earlier report in acute HF patients, in which levels of BNP measured at admission were found to hold equal predictive value for in‐hospital mortality and length of stay 12. Additionally, several key studies have evaluated the predictive value of BNP in Asian populations and showed that BNP is a key predictor of outcomes in these patients 30, 31, 32. Also, NT‐proBNP levels had equal predictive value in both HFpEF and HFrEF.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is in line with an earlier report in acute HF patients, in which levels of BNP measured at admission were found to hold equal predictive value for in‐hospital mortality and length of stay 12. Additionally, several key studies have evaluated the predictive value of BNP in Asian populations and showed that BNP is a key predictor of outcomes in these patients 30, 31, 32. Also, NT‐proBNP levels had equal predictive value in both HFpEF and HFrEF.…”
Section: Discussionsupporting
confidence: 89%
“…IL-6 was found to predict long-term mortality 4,5,7 and long-term cardiac death 6 in chronic HF whereas, in the present study, IL-6 was not found to predict intermediateterm risk of ventricular arrhythmias among HF patients. Yet, none of the previous studies showed a correlation between IL-6 and sudden death, and the majority of the patients in the previous studies had NYHA class III-IV, whereas 81% of the patients in our study had NYHA class I-II.…”
Section: Il-6contrasting
confidence: 81%
“…So far, TNF-α was shown to predict cardiac mortality in patients with NYHA class III-IV, 6 and 1.1-2.7 years all cause mortality in stable HF patients and patients with NYHA III-IV. 7,20 These data together with the negative results of our study suggest that TNF-α may be related to nonarrhythmic death or may still be associated with arrhythmic death among unstable HF patients with NYHA III-IV.…”
Section: Tnf-αmentioning
confidence: 99%
See 2 more Smart Citations